Essentialization of Structural Differences in the Canonical Narratives (Voice of Teacher, 2025)
This paper examines the canonical narratives, The Tempest, Robinson Crusoe and Jane Eyre to uncover the influence of essentialism in representations. I argue that the construction of structural binaries regarding race, gender, class and nationalities in these narratives are the consequences of essentialism that rationalizes unequal relations as natural or essential. Ideologies play the key roles to essentialize the binaries of relations. The racial supremacy, gender hierarchy and class divisions are essentialized to maintain the center-margin power relations. Therefore, to deconstruct the binaries, it is necessary to critique to essentialism and the ideologies that help maintain unequal relations in the name of cultures or other problematic belief systems. To address these issues, the study draws the theoretical support from Gayatri Spivak’s ideas of Strategic Essentialism and Deconstruction. The key finding of this study is that the canonical stories reflect the influence of essentialism as they represent binary relations between classes, races, nationalities and men and women. To alter such relations in representations, the canonical narratives need revisions through the alternative narratives. A Tempest, Foe and Wide Sargasso Sea respectively are examples of alternative representations